2012
DOI: 10.1248/yakushi.12-00234-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Ophthalmic Liposomes for Nucleic Acid Delivery to Posterior Segment of Eye

Abstract: Nucleic acids like siRNA and pDNA are remarkable for treatment of ophthalmic diseases in posterior segment of eye such as age-related macular degeneration (AMD). However, hydrophilic and high molecule compounds are restricted in intraocular distribution through anterior segment of the eye. In addition, the ocular tissue has a blood-retinal barrier which restricts drug delivery thorough systemic administration. Therefore the invasive intravitreal injection has been generally applied for treatment of retinal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In recent years, different topical liposomes have been developed to deliver drugs into the posterior segment of the eye [23][24][25][26][27][28][29][30][31]. For example, fluorescent molecules like 5(6)-carboxyfluorescein and coumarin-6 [23,25,29,30], drugs such as edaravone and diclofenac [26,27], and biomolecules such as nucleic acids [28,31] and bevacizumab (a monoclonal antibody against vascular endothelial growth factor A) [24] have been released into the vitreous body and retina by liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, different topical liposomes have been developed to deliver drugs into the posterior segment of the eye [23][24][25][26][27][28][29][30][31]. For example, fluorescent molecules like 5(6)-carboxyfluorescein and coumarin-6 [23,25,29,30], drugs such as edaravone and diclofenac [26,27], and biomolecules such as nucleic acids [28,31] and bevacizumab (a monoclonal antibody against vascular endothelial growth factor A) [24] have been released into the vitreous body and retina by liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes are an attractive option for nonviral gene therapy. 35 Liposomes, vesicles formed by phospholipid bilayers, are biocompatible and can be tailored for various sizes, release rates, hydrophilicity, and lipophilicity. 36 Furthermore, the lipid bilayer of liposomes can integrate and pass through cell membranes without the need for electroporation.…”
Section: Suprachoroidal Nonviral Gene Deliverymentioning
confidence: 99%
“…Special mention is reserved for the study performed by Davis BM et al This group demonstrated that the topical instillation of eye drops containing annexin A5 associated with liposomes loaded with bevacizumab is able to deliver physiologically significant concentrations of this large therapeutic protein (monoclonal antibody against vascular endothelial growth factor A) into the posterior segment of the eye in animal models (rats and rabbits) [156]. Moreover, liposomes can release genetic material into the vitreous and the retina [160,163].…”
Section: Topical Liposomes For Drug Delivery Into the Posterior Segmementioning
confidence: 99%
“…[155][156][157][158][159][160][161][162][163].Breaking down the Barrier: Topical Liposomes as Nanocarriers for Drug Delivery… DOI: http://dx.doi.org/10.5772/intechopen.86601…”
mentioning
confidence: 99%